On the Causal Relationship Between the Moist Diabatic Circulation and Cloud Rapid Adjustment to Increasing CO2. (26th November 2019) - Dinh, T.; Fueglistaler, S.
Abstract: General circulation models predict that clouds in the atmosphere rapidly adjust to the radiative perturbation of an abrupt increase in atmospheric CO2 concentration on a short time scale of about 10 days. This rapid adjustment consists of an increase of clouds in the boundary layer and a decrease of clouds in the free troposphere. Our focus is the mechanism for the decrease of clouds in the free troposphere, which is the dominating component of cloud rapid adjustment in most general circulation models. We propose that the decrease in clouds in the free troposphere arises from the causal relationship between the moist diabatic circulation and the production of condensates that forms clouds in moist processes. As CO2 concentration increases, tropospheric radiative cooling is reduced, resulting in weakening of the moist diabatic circulation and a decrease in precipitation. As the hydrologic cycle weakens and the moist processes involving phase change of water vapor to form the condensates in the atmosphere lessen, the mass of cloud condensates decreases. This decrease in cloud condensates can be predicted from the decrease in the radiative subsidence mass flux, which is a metric for the strength of the moist diabatic circulation in the free troposphere. Plain Language Summary: Climate models predict that the global average precipitation and clouds decrease rapidly on a short time scale of about 10 days following an abrupt increase in atmospheric CO2 concentration. We demonstrate that these rapid decreases in global precipitation and clouds are manifestations of the weakening of the hydrologic cycle, which is directly forced by the perturbation of the atmosphere's radiative energy budget due to CO2 increase. Key Points: The hydrologic cycle weakens during rapid adjustment due to a reduction in tropospheric radiative cooling associated with CO2 increase The mass of cloud condensates decreases during rapid adjustment as the production of condensates decreases in a weakened hydrologic cycle The decrease in cloud condensates is predicted from the decrease in the radiative subsidence mass flux of the moist diabatic circulation